Islamic Banks in Morocco: Balancing Religious Monopoly and Financial Pragmatism - Haddad, Abderrahmane (Islamic Banking and Finance Review, 2026)
The objective of this research is to demonstrate how Moroccan banking legislation has succeeded in establishing Islamic banks in order to benefit materially from them while controlling their religious character and putting it at the service of the political and social stability of the country. This research found that Moroccan banking legislation has achieved a smooth integration of Islamic products by controlling their religious aspect through the establishment of several legal guarantees and guardrails in order not to threaten the political and social stability of the country. By reading this study, readers will be able to discover the underside of the Moroccan Islamic banking legislation, which could constitute a source of inspiration for other countries. Methodologically, we employed a critical analysis of legal discourse that combines an examination of the rules with an analysis of power dynamics and underlying issues. We also drew on a second database consisting of empirical data and official statistics.